The Role of Action Games in The Formation of Athletic Skills of Teenage Volleyball Players - Ochilov Sherzod Jumaniyazovich (Zien Journals, 2024)
This article analyzes the scientific basis for the formation of technical elements that can be performed by jumping using action games in the formation of jumping skills of teenage volleyball players in training sessions.
Keywords: volleyball training; technical-tactical combinations